MATEMÁTICA FINANCEIRA: UMA PERSPECTIVA USANDO RECORRÊNCIAS LINEARES - BRAZ TEODORO JIMÉNEZ MARTINS (2023)
The main objective of this work is to study and link the linear recurrences with the financial math. For such, initially a detailed study of the recurrences of first and second order has been made. Financial Education at BNCC has been discussed about and the deductions of formulas of composed interests, Price Amortization System and Constant Amortization System (SAC), for linear recurrences. Besides, connections between linear recurrences and concepts of linear algebra, such as: vectorial space, basis and dimension, concluding that the set of solutions of a recurrence is a vectorial space. Besides, some economic models that have been presented may be studied by recurrence equations. At last, we have presented some problematic situations of financial mathematics that may be worked in the classroom, like composed interests, amortization and financial applications with monthly reports. Keywords: Linear Recurrences of First and Second Order, Financial Education, Financial Math, Economic Models.